PISA, reading comprehension and other discussions (Journal of Parents and Teachers, 2014)
What obsessions does PISA report develop? In this article there is a consideration about results and misinterpretations sometimes given by media. It is required to know how to interpret statistic data in a correct way. Sample size also condition results and this way differences of less than five points may be caused by random mistakes. Therefore, drawing final conclusions and generalising in every situation is not correct.
Keywords: opinion; PISA; international report of education; reflection; teaching.